Ti-Zr-Cu-Ni-Mn high-entropy brazing filler metal and preparation method and application thereof

By using Ti-Zr-Cu-Ni-Mn high-entropy brazing during the brazing process, the problem of brittle intermetallic compounds in the brazing of TiAl alloy and Ni-based high-temperature alloy is solved, and the mechanical properties and heat resistance of the joints are significantly improved.

CN119609449AActive Publication Date: 2025-03-14SHENYANG LIGONG UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411766798.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-14
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

TiAl alloy and Ni-based high-temperature alloy are prone to produce brittle intermetallic compounds during the brazing process, resulting in poor mechanical properties of the welded joints.

Method used

Ti-Zr-Cu-Ni-Mn high-entropy brazing is used, with chemical compositions of Ti: 15%-25%, Zr: 15%-25%, Cu: 15%-25%, Ni: 15%-25%, Mn: 15%-25%, Mn: 15%-25%. The high entropy effect is introduced through the design theory of high-entropy alloys, and the brazing composition is optimized to improve the microstructure of the joint and inhibit the precipitation of the brittle phase.

Benefits of technology

By using Ti-Zr-Cu-Ni-Mn high entropy brazing, the room temperature shear strength of the brazed joints of TiAl alloy and Ni-based high temperature alloy is significantly improved to reach 214 MPa, and the heat resistance and economicality of the joints are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119609449A_ABST
    Figure CN119609449A_ABST
Patent Text Reader

Abstract

The invention discloses a Ti-Zr-Cu-Ni-Mn high-entropy brazing filler metal and a preparation method and a brazing method thereof, relates to a high-entropy brazing filler metal for welding a TiAl alloy and a Ni-based high-temperature alloy and a preparation method and a brazing method thereof, and belongs to the technical field of welding materials. The brazing filler metal is composed of, by atomic percent, 20% of Ti, 20% of Zr, 20% of Cu, 20% of Ni and 20% of Mn. The preparation method comprises the following steps: burdening according to the content of the components, and smelting the raw materials through an electric arc smelting method to obtain a brazing filler metal master alloy ingot; and after the alloy ingot is crushed into small blocks, the Ti-Zr-Cu-Ni-Mn high-entropy brazing filler metal is prepared through a single-roller melt-spinning method. The liquidus temperature of the high-entropy brazing filler metal is 1130 DEG C, and the high-entropy brazing filler metal has the advantages of being low in cost, easy and convenient to assemble, good in wettability with base metal, capable of easily forming a brazing joint with excellent performance with TiAl alloy and Ni-based high-temperature alloy and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of welding, and in particular relates to a Ti-Zr-Cu-Ni-Mn high-entropy solder and a preparation method and application thereof. Background Art

[0002] Lightweighting of aerospace weapons and equipment is an urgent need for the country's major strategic development. TiAl alloy has both lightweight and heat-resistant properties and is widely considered to be an ideal material for manufacturing important hot-end components such as aerospace. It is very difficult and much more economical to use TiAl alloy alone to process the entire component. However, connecting TiAl alloy and Ni-based superalloys together can complement each other in terms of cost reduction and performance improvement. Since the two materials have obvious differences in composition, obtaining a weld joint with good welding quality is the key to effectively connecting TiAl alloy and Ni-based superalloy.

[0003] Brazing has the advantages of little effect on the structure and properties of the parent material, small stress and deformation, and is suitable for the connection of TiAl alloy and Ni-based high-temperature alloy. When brazing is used for connection, the structure and properties of the brazed joint are directly affected by the brazing filler metal. The main elements of the two parent materials, Ti, Al, and Ni, easily react to form hard and brittle Ti-Ni and Ti-Al-Ni intermetallic compounds, causing crack initiation and thus deteriorating the mechanical properties of the joint. Summary of the invention

[0004] In view of the problem that brittle intermetallic compounds are easily generated during the brazing process of TiAl alloy and Ni-based high-temperature alloy in the prior art, the present invention provides a Ti-Zr-Cu-Ni-Mn high-entropy brazing filler metal and its preparation method and application, borrowing the design theory of high-entropy alloy, introducing the high-entropy effect to optimize the composition of the brazing filler metal to improve the microstructure of the joint and inhibit the precipitation of the brittle phase. The technical solution of the present invention is as follows: The present invention provides a Ti-Zr-Cu-Ni-Mn high entropy solder, the chemical composition of the high entropy solder and the components in atomic percentage are as follows: Ti: 15%-25%, Zr: 15%-25%, Cu: 15%-25%, Ni: 15%-25%, Mn: 15%-25%.

[0005] The preparation method of the above Ti-Zr-Cu-Ni-Mn high entropy solder is carried out according to the following steps: Step 1: Convert the atomic percentage of the high entropy solder into mass percentage and weigh the raw materials. All raw materials of each element are pure metals with a purity of more than 99.9%; Step 2: Place the raw materials prepared in step 1 into a copper crucible in a vacuum arc furnace for smelting, and repeatedly remelt 4-5 times to obtain a master alloy ingot of high entropy solder, wherein: The element Ti is placed at the bottom of the crucible; Elemental Cu should avoid direct contact with the crucible; The remaining elements are placed in the crucible in order from low to high melting points; Step three: crush the master alloy ingot of the high entropy solder in step two into fragments, heat and melt the master alloy ingot fragments of the high entropy solder in a rapid solidification device, and then prepare Ti-Zr-Cu-Ni-Mn high entropy solder by a single-roller strip method, wherein the solder is in the form of debris.

[0006] Furthermore, in the preparation method of the above-mentioned Ti-Zr-Cu-Ni-Mn high entropy solder, in step 1, oxides and oil stains on the surface of the raw materials must be removed before weighing the raw materials.

[0007] Furthermore, in the preparation method of the above-mentioned Ti-Zr-Cu-Ni-Mn high entropy solder, in the smelting process described in step 1, the vacuum degree of the vacuum melting furnace is pumped to 3.5×10 -3 After the pressure drops below Pa, argon is filled in and the process is carried out under the protection of argon atmosphere.

[0008] Furthermore, in the preparation method of the above-mentioned Ti-Zr-Cu-Ni-Mn high entropy solder, in step three, the method of crushing the mother alloy ingot into small pieces is mechanical crushing.

[0009] Furthermore, in the preparation method of the above-mentioned Ti-Zr-Cu-Ni-Mn high-entropy solder, the rapid solidification device in step three is a vacuum melting belt spinning machine, and the heating and melting refers to putting the mother alloy ingot fragments into a quartz tube, and then placing it into the vacuum melting belt spinning machine, and melting it by induction melting.

[0010] Furthermore, in the preparation method of the above-mentioned Ti-Zr-Cu-Ni-Mn high-entropy solder, when the single-roller spinning method is used for preparation in step three, the preparation process parameters are specifically as follows: the rotation frequency of the rotating copper roller is 30-40 Hz, the distance between the melt outlet and the copper roller surface is 0.4-0.5 mm, the amount of argon protective gas filled is 300-400 mbar, and the argon pressure used for melt injection is 100-200 mbar.

[0011] The present invention also discloses a method for brazing TiAl alloy and Ni-based high-temperature alloy using the above-mentioned Ti-Zr-Cu-Ni-Mn high-entropy brazing filler metal, which is carried out according to the following steps: The surface of the base material to be welded was polished with sandpaper of the same mesh to remove surface impurities and oxides. The Ti-Zr-Cu-Ni-Mn high entropy brazing filler metal was placed between the surfaces of the base material to be welded and then put into a vacuum brazing furnace. It was heated to 1170 °C in a vacuum environment and kept warm for 30 min. After cooling to 200 °C, the workpiece was taken out to complete the brazing.

[0012] In the above method of brazing TiAl alloy and Ni-based high-temperature alloy using Ti-Zr-Cu-Ni-Mn high-entropy brazing filler metal, the sandpaper with the same mesh size is specifically 80 mesh, the liquidus temperature of the Ti-Zr-Cu-Ni-Mn high-entropy brazing filler metal is 1130°C, and the contact surface area of ​​the brazing joint parent metal is 70 mm 2 The added solder mass is 60 mg to ensure that the solder gap can be fully filled.

[0013] In the above method of brazing TiAl alloy and Ni-based high temperature alloy using Ti-Zr-Cu-Ni-Mn high entropy brazing filler metal, the vacuum environment of the vacuum brazing furnace refers to a vacuum degree of less than 5×10 -4 Pa, and the heating and cooling rates are both 10 °C / min.

[0014] Ti and Ni, as the main components of TiAl alloy and Ni-based high-temperature alloy respectively, can make the solder maintain good wettability and fluidity on the surface of both base materials at the same time; at the same time, Ti and Ni can undergo eutectic reaction to form a low-melting point eutectic and reduce the melting point of the solder.

[0015] Zr and Cu are infinitely miscible with Ti and Ni elements respectively, and have low melting points, which is beneficial to further reduce the melting point of the alloy system; among them, due to the large size difference between Zr and Ti, Zr can enhance the performance of Ti alloy as a solid solution.

[0016] Mn has a low melting point and low price. It is a eutectic β-stabilizing element and can improve the strength and plasticity of Ti alloys.

[0017] The advantages and beneficial effects of the present invention are as follows: (1) Control of the melting temperature of the solder: During the brazing process, the solder must melt while the base material must not melt. Therefore, it is crucial to ensure that the melting temperature of the solder is within an appropriate range when designing the composition. The Ti-Zr-Cu-Ni-Mn high entropy solder described in the present invention, wherein Ni, Mn and Cu have relatively low melting points of 1455°C, 1246°C and 1084.62°C, respectively, is beneficial for controlling the melting point of the solder. At the same time, Ti and Zr can undergo eutectic reaction with Cu and Ni to lower the melting point of the solder, so that the solder has a suitable melting temperature. The liquidus temperature of the Ti-Zr-Cu-Ni-Mn high entropy solder provided by the present invention is lower than that of the base material, which is 1130°C.

[0018] (2) Wettability of solder and parent material: During the brazing process, after the solder melts into liquid, the liquid solder will wet, fill, and interact with the parent material surface, and form a strong joint after cooling and solidification, thereby connecting the parent materials. Therefore, good wettability of the liquid solder on the parent material surface is a basic condition for the solder to fill the gap and form a brazed joint. The Ti-Zr-Cu-Ni-Mn high entropy solder described in the present invention, in which Zr and Cu can be infinitely dissolved with the main elements Ti and Ni in the parent material respectively, can significantly reduce the interfacial tension, thereby significantly improving the wettability of the solder. The Ti-Zr-Cu-Ni-Mn high entropy solder provided by the present invention exhibits good wettability on both parent materials; at the same time, the metal component of the parent material contained in the solder can reduce the dissolution of the parent material into the solder, and prevent the excessive dissolution of the parent material from deteriorating the fluidity of the liquid solder, resulting in the inability to fill the joint gap.

[0019] (3) Interaction between the brazing filler metal and the base metal: During the brazing process, due to a series of metallurgical processes such as dissolution, diffusion, solidification and crystallization between the base metal and the brazing filler metal, the structure of the brazed joint is not single, and the performance of the joint becomes extremely complex. During the brazing process of TiAl alloy and Ni-based high-temperature alloy, brittle intermetallic compounds are easily generated, resulting in deterioration of the performance of the brazed joint. Therefore, inhibiting the generation of intermetallic compounds at the joint is the key to improving the strength of the joint. The Ti-Zr-Cu-Ni-Mn high-entropy brazing filler metal described in the present invention, due to the uniqueness of the high-entropy alloy, the high-entropy effect in thermodynamics enables the high-entropy alloy to inhibit the generation of ordered intermetallic compounds during the solidification process, and it is easy to generate a multi-principal solid solution and is more stable. The room temperature shear strength of the dissimilar brazing joint of the TiAl alloy and the Ni-based high-temperature alloy made by the Ti-Zr-Cu-Ni-Mn high-entropy brazing filler metal provided by the present invention reaches 214 MPa.

[0020] (4) The solder of the present invention has uniform composition and is in the form of crumbs, which is convenient for assembly and more convenient for controlling the width of the weld. Compared with other solders used for brazing TiAl alloys and Ni-based high-temperature alloys, the raw material cost of the solder of the present invention is significantly reduced, effectively controlling the production cost. At the same time, the liquidus temperature of the high-entropy alloy solder proposed in the present invention is 1130 °C, which ensures good heat resistance of the joint and can meet the working requirements of the joint at high temperatures. (5) The brazing method described in the present invention is carried out in a vacuum, which can avoid the adverse effects of air on the joint performance. Compared with other welding methods, it does not require the application of pressure and the process is simpler. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The scanning electron microscope microstructure morphology of the Ti-Zr-Cu-Ni-Mn high entropy solder master alloy ingot prepared in Example 1; Figure 2 The scanning electron microscope microstructure morphology of the cross section of the joint of the TiAl alloy and the Ni-based high-temperature alloy K416B brazed with the Ti-Zr-Cu-Ni-Mn high-entropy brazing filler metal in Example 1; Figure 3 This is the scanning electron microscope microstructure morphology of the cross section of the joint where the TiAl alloy and the Ni-based high-temperature alloy K416B are brazed with Ti-Zr-Cu-Ni brazing filler metal in Comparative Example 1. DETAILED DESCRIPTION

[0022] The preparation method and application of the Ti-Zr-Cu-Ni-Mn high entropy solder of the present invention are described in detail below with reference to the accompanying drawings and specific embodiments. Example 1

[0023] The present embodiment provides a Ti-Zr-Cu-Ni-Mn high entropy solder, whose chemical composition, in atomic percentage, comprises: Ti: 20%, Zr: 20%, Cu: 20%, Ni: 20%, Mn: 20%, and its preparation method comprises the following steps: preparing 30 g of metal raw materials, specifically: weighing 4.54 g of Ti single substance with a purity of more than 99.9% and from which oxides and impurities have been removed, 8.65 g of Zr single substance, 6.03 g of Cu single substance, 5.57 g of Ni single substance, and 5.21 g of Mn single substance.

[0024] Put the metal elements into the copper crucible of the vacuum arc furnace in the order of melting point from low to high. The Cu element should avoid contact with the crucible. The vacuum degree of the furnace chamber is pumped to 3.5×10 -3 After the temperature drops below Pa, argon is filled in and smelting is carried out under the protection of argon atmosphere. This process is repeated 4 times to obtain a master alloy ingot of high entropy solder.

[0025] The obtained high entropy solder master alloy ingot was mechanically crushed into small pieces, and the pieces of suitable size were selected and ultrasonically cleaned in anhydrous ethanol for 10 minutes and then blown dry. The cleaned pieces were placed in a pointed quartz tube and then placed in the induction coil of the vacuum melting belt spinning machine. The position of the quartz tube was adjusted to ensure that the distance between the quartz tube outlet and the copper roller surface was 0.4 mm during the spraying. The vacuum degree in the furnace chamber was drawn to 3.5×10 -3 Pa, fill the furnace chamber and the gas tank with 300 mbar of argon at the same time. When the pressure gauge value is stable, fill the gas tank with argon again. The argon pressure for melt injection is 150 mbar. Set the rotation frequency of the copper roller to 38 Hz. Turn on the main switch of the induction power supply, adjust the power of the induction power supply, and melt the brazing master alloy ingot fragments. When the fragments in the tube emit a dazzling white light and are completely melted and uniform, the melt can be sprayed after the melt fluctuates. The melt is sprayed onto the surface of the high-speed rotating copper roller and quickly cooled to obtain a high-entropy brazing material in the form of debris.

[0026] like Figure 1 Shown is the scanning electron microscope microstructure morphology of the Ti-Zr-Cu-Ni-Mn high entropy solder master alloy ingot prepared in Example 1.

[0027] The Ti-Zr-Cu-Ni-Mn high entropy brazing filler metal prepared in this embodiment is used to braze TiAl alloy and Ni-based high temperature alloy K416B. The specific brazing method is as follows: The surfaces of TiAl alloy and Ni-based superalloy K416B to be welded were polished with 80# sandpaper to remove surface impurities and oxides, and then ultrasonically cleaned in anhydrous ethanol for 10 min and then blown dry. 60 mg of Ti-Zr-Cu-Ni-Mn high entropy brazing filler metal was placed between the surfaces of TiAl alloy and Ni-based superalloy K416B to be welded for assembly, specifically: TiAl alloy / Ti-Zr-Cu-Ni-Mn high entropy brazing filler metal / Ni-based superalloy K416B in the order from top to bottom. The assembled parts to be welded were placed in a vacuum brazing furnace. When the vacuum degree of the brazing furnace was less than 5×10 -4 Pa environment, heated to 1170 ℃ at a rate of 10 ℃ / min, kept warm for 30 min, cooled to 200 ℃ at a rate of 10 ℃ / min, and then the workpiece was taken out to complete the brazing. The shear strength of the brazed joint at room temperature is 214 MPa.

[0028] like Figure 2 Shown is the scanning electron microscope microstructure morphology of the cross section of the joint of the TiAl alloy and the Ni-based high-temperature alloy K416B brazed with Ti-Zr-Cu-Ni-Mn high-entropy brazing filler metal in Example 1. Comparative Example 1

[0029] This comparative example provides a commercial Ti-Zr-Cu-Ni solder, whose chemical composition, in terms of mass percentage, comprises: Ti: 37.5%, Zr: 37.5%, Cu: 15%, Ni: 10%, and its preparation method comprises the following steps: preparing 30 g of metal material, specifically: weighing 11.25 g of Ti single substance with a purity of more than 99.9% and from which oxides and impurities have been removed, 11.25 g of Zr single substance, 4.50 g of Cu single substance, and 3.00 g of Ni single substance.

[0030] Put the metal elements into the copper crucible of the vacuum arc furnace in the order of melting point from low to high. The Cu element should avoid contact with the crucible. The vacuum degree of the furnace chamber is pumped to 3.5×10 -3 After the temperature drops below Pa, argon is filled in and smelting is carried out under the protection of argon atmosphere. This process is repeated 4 times to obtain a master alloy ingot of high entropy solder.

[0031] The obtained high entropy solder master alloy ingot was mechanically crushed into small pieces, and the pieces of suitable size were selected and ultrasonically cleaned in anhydrous ethanol for 10 minutes and then blown dry. The cleaned pieces were placed in a pointed quartz tube and then placed in the induction coil of the vacuum melting belt spinning machine. The position of the quartz tube was adjusted to ensure that the distance between the quartz tube outlet and the copper roller surface was 0.4 mm during the spraying. The vacuum degree in the furnace chamber was drawn to 3.5×10 -3 Pa, fill the furnace chamber and the gas tank with 300 mbar of argon at the same time. When the pressure gauge value is stable, fill the gas tank with argon again. The argon pressure for melt injection is 150 mbar. Set the rotation frequency of the copper roller to 38 Hz. Turn on the main switch of the induction power supply, adjust the power of the induction power supply, and melt the solder master alloy ingot fragments. When the fragments in the tube emit a dazzling white light and are completely melted and uniform, the injection can begin after the melt fluctuates. The melt is sprayed onto the surface of the high-speed rotating copper roller and quickly cooled to obtain a foil-shaped high-entropy solder; The Ti-Zr-Cu-Ni brazing filler metal prepared in this comparative example is used to braze TiAl alloy and Ni-based high temperature alloy K416B. The specific brazing method is as follows: The surfaces of TiAl alloy and Ni-based superalloy K416B to be welded were polished with 80-grit sandpaper to remove surface impurities and oxides, and then ultrasonically cleaned in anhydrous ethanol for 10 min and then blown dry. 60 mg of brazing filler metal was cut into pieces and placed between the surfaces of TiAl alloy and Ni-based superalloy K416B to be welded for assembly, specifically: TiAl alloy / Ti-Zr-Cu-Ni brazing filler metal / Ni-based superalloy K416B from top to bottom. The assembled parts to be welded were placed in a vacuum brazing furnace. When the vacuum degree of the brazing furnace was less than 5×10 -4 Pa environment, heated to 940 ℃ at a rate of 10 ℃ / min, kept warm for 30 min, cooled to 200 ℃ at a rate of 10 ℃ / min, and then the workpiece was taken out to complete the brazing. The shear strength of the brazed joint at room temperature is 132MPa.

[0032] like Figure 3 The figure shows the scanning electron microscope microstructure of the cross section of the joint of the TiAl alloy and the Ni-based high temperature alloy K416B brazed with Ti-Zr-Cu-Ni brazing filler metal in Comparative Example 1. In summary, through comparison, it can be concluded that the Ti-Zr-Cu-Ni-Mn high entropy brazing filler metal provided by the present invention is used for brazing TiAl alloy and Ni-based high-temperature alloy to obtain a higher joint shear strength than the existing brazing filler metal.

[0033] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A Ti-Zr-Cu-Ni-Mn high entropy solder, characterized in that: The chemical composition of the high entropy solder comprises the following components in atomic percentage: Ti: 15%-25%, Zr: 15%-25%, Cu: 15%-25%, Ni: 15%-25%, Mn: 15%-25%.

2. A method for preparing the Ti-Zr-Cu-Ni-Mn high entropy solder according to claim 1, characterized in that: The following steps are involved: Step 1: Convert the atomic percentage of the high entropy solder into mass percentage and weigh the raw materials. All raw materials of each element are pure metals with a purity of more than 99.9%; Step 2: Place the raw materials prepared in step 1 into a copper crucible in a vacuum arc furnace for smelting, and repeatedly remelt 4-5 times to obtain a master alloy ingot of high entropy solder, wherein: Element Ti is placed at the bottom of the crucible; Elemental Cu should avoid direct contact with the crucible; The remaining elements are placed in the crucible in order from low to high melting points; Step three: crush the master alloy ingot of the high entropy solder in step two into fragments, heat and melt the master alloy ingot fragments of the high entropy solder in a rapid solidification device, and then prepare Ti-Zr-Cu-Ni-Mn high entropy solder by a single-roller strip method, wherein the solder is in the form of debris.

3. The method for preparing the Ti-Zr-Cu-Ni-Mn high entropy solder according to claim 2, characterized in that: In the smelting process described in step 1, the vacuum degree of the vacuum melting furnace is evacuated to 3.5×10 -3 After the pressure drops below Pa, argon is filled in and the process is carried out under the protection of argon atmosphere.

4. The method for preparing the Ti-Zr-Cu-Ni-Mn high entropy solder according to claim 2, characterized in that: Step 3: The method of breaking the master alloy ingot into small pieces is mechanical crushing.

5. The method for preparing the Ti-Zr-Cu-Ni-Mn high entropy solder according to claim 2, characterized in that: The rapid solidification device in step 3 is a vacuum melting belt spinning machine. Heating and melting refers to placing the mother alloy ingot fragments into a quartz tube, and then placing it into the vacuum melting belt spinning machine to melt it by induction melting.

6. The method for preparing the Ti-Zr-Cu-Ni-Mn high entropy solder according to claim 2, characterized in that: When the single-roller belt-spinning method is used for preparation in step three, the specific preparation process parameters are: the rotation frequency of the rotating copper roller is 30-40 Hz, the distance between the melt outlet and the copper roller surface is 0.4-0.5 mm, the amount of argon protective gas filled is 300-400 mbar, and the argon pressure used for melt spraying is 100-200 mbar.

7. A method for brazing TiAl alloy and Ni-based high-temperature alloy using the Ti-Zr-Cu-Ni-Mn high-entropy brazing filler metal according to claim 1, characterized in that: Follow these steps: The surface of the base material to be welded was polished with sandpaper of the same mesh to remove surface impurities and oxides. The Ti-Zr-Cu-Ni-Mn high entropy brazing filler metal was placed between the surfaces of the base material to be welded and then put into a vacuum brazing furnace. It was heated to 1170 °C in a vacuum environment and kept warm for 30 min. After cooling to 200 °C, the workpiece was taken out to complete the brazing.

8. The method for brazing TiAl alloy and Ni-based high-temperature alloy with Ti-Zr-Cu-Ni-Mn high-entropy brazing filler metal according to claim 7, characterized in that: The sandpaper with the same mesh size is specifically 80 mesh, the liquidus temperature of the Ti-Zr-Cu-Ni-Mn high entropy solder is 1130 °C, and the contact surface area of ​​the parent material of the brazed joint is 70 mm 2 The added solder mass is 60 mg to ensure that the solder gap can be fully filled.

9. The method for brazing TiAl alloy and Ni-based high-temperature alloy using Ti-Zr-Cu-Ni-Mn high-entropy brazing filler metal according to claim 7, wherein the vacuum condition of the vacuum brazing furnace is less than 5×10 -4 Pa, and the heating and cooling rates are both 10 °C / min.

Citation Information

Patent Citations

  • Brazing process for vacuum brazing TiAl-based alloy through amorphous-state Ti-Zr-Cu-Ni brazing filler metal

    CN108453332A

  • High-temperature-resistant solder capable of being used for welding gamma-tial alloy and welding process thereof

    CN110355496A

  • Gold-base high-entropy brazing filler metal

    CN110919232A

  • High-melting-point Ti-Zr-Cu-Ni alloy brazing material

    CN111843288A

  • Ti-Zr-Cu-Ni amorphous brazing filler metal as well as preparation method and application thereof

    CN112719688A